(untitled) (Journal of Applied Membrane Science & Technology, 2025)
Membrane technology plays a crucial role in desalination and water treatment, offering efficient solutions to water scarcity and contamination challenges. The book “Experimental Methods for Membrane Applications in Desalination and Water Treatment,” edited by Sergio G. Salinas-Rodríguez and Loreen O. Villacorte, serves as a comprehensive guide to experimental techniques, performance assessment, and fouling control in membrane-based water treatment processes. Published by IWA Publishing in 2024, this book comprises 19 chapters that cover a wide range of membrane applications in both academic and industrial settings.